The Influence of Organizational Culture, Situational Leadership and Organizational Commitment on Employee Work Productivity at PT Maluku Graha Motor - Lawalatta, Merlyn; Lewaherilla, Novalien C.; Pentry, Gerrit M (SEAN Institute, 2024)
The purpose of this study is to examine the influence of organizational culture, situational leadership and organizational commitment on employee work productivity. The study took place at PT Maluku Graha Motor. The sample taken was 55 respondents. The data taken was primary data, and the research method used was a quantitative method. The analysis tool used was Multiple Linear Regression. The results of the study prove that organizational culture, situational leadership and organizational commitment have a significant effect on employee work productivity both partially and simultaneously.